2007
DOI: 10.1038/sj.jhh.1002192
|View full text |Cite
|
Sign up to set email alerts
|

Home-measured blood pressure is more strongly associated with electrocardiographic left ventricular hypertrophy than is clinic blood pressure: the Finn-HOME study

Abstract: Electrocardiographic evidence of left ventricular hypertrophy (ECG-LVH) has a grave prognostic significance in hypertensive patients. The purpose of our study was to assess whether ECG-LVH is more strongly associated with home-measured blood pressure (BP) than with clinic BP, and whether the correlation between home BP and ECG-LVH increases with the number of home measurements performed. We studied a representative sample of the general adult population (1989 subjects 45-74 years of age) in Finland. Subjects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0
1

Year Published

2008
2008
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 29 publications
2
24
0
1
Order By: Relevance
“…6 Studies in nondiabetic hypertensives have shown HBP monitoring to be as good as ambulatory monitoring in predicting albuminuria and left ventricular hypertrophy. [23][24][25][26] To our knowledge, no published study provided a direct comparison of home with ABP in terms of their association with albuminuria in type 1 diabetes. It is clear that the development of albuminuria and its relationship with the rise in BP is fundamentally different in type 1 diabetes compared with type 2.…”
Section: Discussionmentioning
confidence: 99%
“…6 Studies in nondiabetic hypertensives have shown HBP monitoring to be as good as ambulatory monitoring in predicting albuminuria and left ventricular hypertrophy. [23][24][25][26] To our knowledge, no published study provided a direct comparison of home with ABP in terms of their association with albuminuria in type 1 diabetes. It is clear that the development of albuminuria and its relationship with the rise in BP is fundamentally different in type 1 diabetes compared with type 2.…”
Section: Discussionmentioning
confidence: 99%
“…The clinical usefulness of BP measurement at home by semiautomated devices has been investigated over the past 30 years. Several studies have shown that home BP (HBP) measurement, by providing multiple BP recordings under relatively stable conditions and avoiding the so-called 'white-coat effect', is superior to office or clinic BP measurement in terms of reliability, 3 correlation with organ damage 4,5 and predictive value of cardiovascular events. [6][7][8][9] In addition, HBP has been shown to be free of the placebo effect, to improve patients' compliance and to be useful in detecting white-coat and masked hypertension phenomena.…”
mentioning
confidence: 99%
“…4 Some studies have shown that hypertension for several years is associated with the development of ECG abnormalities that in turn are related to a higher left ventricular mass among patients without ischemic heart disease. [5][6][7][8] These abnormalities are also associated with hypertension [9][10][11] and a poor prognosis. 3,4,12 Measuring blood pressure (BP) at home (home BP) allows the collection of multiple measurements under controlled conditions, and it is more reliable than conventional (office) BP measurements, because bias arising from both observer and regression dilution is avoided and the white-coat effect is eliminated.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Cross-sectional and a prospective cohort studies have found that home BP measurement has stronger power for predicting target organ damage, morbidity and mortality than office BP measurement. 11,[15][16][17][18][19] Tsunoda et al found that the degree of LVH determined by echocardiography was more closely associated with home than with office BP values among 209 hypertensive Japanese patients. 15 However, the relationship between home BP and LVH determined by ECG among treated patients in Japan is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation